Restorative Justice for Juvenile Drugs Use in Indonesian Court: A Criminological Approach - Dina Imam Supaat (Lex Publica, 2022)
In Indonesia there are still many children who have been sentenced after the enactment of the Law on the Juvenile Criminal Justice System and other regulations. A question arises as to whether there are any obstacles in the application of Supreme CourtRegulation (PERMA) Number 4 of 2014. This paper reviews restorative justice for criminal juvenile drug use users. The method used in this research is a normative juridical approach using a case approach and a statute approach where the research is carried out by examining library materials which are secondary data. The results of the study show that PERMA Number 4 of 2014 regulates diversion against children whose charges are in the form of subsidiary, alternative, cumulative, or combination (combined). One of which is punishable by under 7 (seven) years in prison. Furthermore, PERMA No. 4 of 2014 has not fully provided legal protection for children, especially perpetrators of drug use crimes, so that PERMA needs further regulation in accordance with the provisions to avoid contradictions. Therefore, there is a need for consolidation between law enforcers to formulate legal certainty from the juvenile justice system.